Oral communication competences for learning english language, related to the use of the tecnology in kindergarten in Aserrio Elementary School, Bugaba Chiriquí, 2011 - Vásquez Moreno, Angela Dianeth (UDELAS, 2011)
Who wants to transmit a message needs to speak clearly, spontaneously and with coherence all the time in order to the receiver understands the message, for this reason this beautiful project makes emphasis in oral communiction competence.